Biphenyl‐Derived Phosphepines as Chiral Nucleophilic Catalysts: Enantioselective [4+1] Annulations To Form Functionalized Cyclopentenes1. Issue 48 (6th October 2014) - Ziegler, Daniel T.; Riesgo, Lorena; Ikeda, Takuya; Fujiwara, Yuji; Fu, Gregory C.
Abstract Because of the frequent occurrence of cyclopentane subunits in bioactive compounds, the development of efficient catalytic asymmetric methods for their synthesis is an important objective. Introduced herein is a new family of chiral nucleophilic catalysts, biphenyl‐derived phosphepines, and we apply them to an enantioselective variant of a useful [4+1] annulation. A range of one‐carbon coupling partners can be employed, thereby generating cyclopentenes which bear a fully substituted stereocenter [either all‐carbon or heteroatom‐substituted (sulfur and phosphorus)]. Stereocenters at the other four positions of the cyclopentane ring can also be introduced with good stereoselectivity. An initial mechanistic study indicates that phosphine addition to the electrophilic four‐carbon coupling partner is not the turnover‐limiting step of the catalytic cycle.